Cytologic features in vitreous preparations of patients with suspicion of intraocular lymphoma. Issue 1 (25th October 2013) - Rodriguez, Erika F.; Sepah, Yasir J.; Jang, Hyun Soo; Ibrahim, Mohamed; Nguyen, Quan Dong; Rodriguez, Fausto J.
<x xml:space="preserve">Abstract</x> Intraocular lymphoma may occur, primarily with or without overt parenchymal CNS lymphoma or secondarily from a variety of other lymphomas. The diagnosis is frequently based on cytologic features and/or a limited panel of ancillary techniques. Twenty‐seven cytology samples from the vitreous preparations of 20 patients with clinical suspicion or histopathologic diagnoses of lymphoma were retrospectively reviewed (2007–2011). Floaters and decreased visual acuity were the most common ocular symptoms. Sixteen (of 20) patients had at least one cytology that was "positive" or "suspicious" for lymphoma (F = 10; M = 6, median age = 71 years, range = 52–82). Involvement was limited to the eye in half of the cases (n = 8). Seven patients had CNS involvement, and three had systemic lymphoma. Cytologic specimens were classified as large B cell lymphoma (LBCL) (n = 13), suspicious for LBCL (n = 5), atypical/negative (n = 5), and consistent with NK‐T cell lymphoma (n = 1). Three cytologic samples were acellular. Cytologic findings included increased cellularity (high n = 7, moderate n = 7), large to medium (n = 19) cell size, marked nuclear irregularities (n = 12), frequent apoptosis (n = 7), lymphoglandular bodies (n = 12), and necrosis (n = 12). Easily identifiable mitotic figures were present in two cases. CD20 immunocytochemistry performed in 15 cases with available cell blocks/destained cytospins preparations, was confirmatory in 8 cases. Cytologic evaluation of intraocular lymphoma is possible in vitreous specimens. Extraocular involvement was not present in half of the cases. The most useful cytologic features include increased cellularity, necrosis, and nuclear enlargement. Ancillary immunocytochemical studies are useful and support the morphologic impression in a subset of cases. Diagn. Cytopathol. 2014;42:37–44. © 2013 Wiley Periodicals, Inc.